2020
DOI: 10.3389/fneur.2020.00432
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls in Scalp High-Frequency Oscillation Detection From Long-Term EEG Monitoring

Abstract: Aims: Intracranially recorded high-frequency oscillations (>80 Hz) are considered a candidate epilepsy biomarker. Recent studies claimed their detectability on the scalp surface. We aimed to investigate the applicability of high-frequency oscillation analysis to routine surface EEG obtained at an epilepsy monitoring unit.Methods: We retrospectively analyzed surface EEGs of 18 patients with focal epilepsy and six controls, recorded during sleep under maximal medication withdrawal. As a proof of principle, the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 90 publications
(110 reference statements)
0
16
0
Order By: Relevance
“…First of all, there are physiological HFOs ( 21 ) and spurious artifacts ( 13 , 22 ) that could mimic the presence of pathological HFOs and share the same frequency range ( 23 , 24 ), which complicates the distinction of clinically relevant HFOs from artifactual or normal ones ( 25 ). When defined only by the occurrence rate, physiological HFOs cannot be disentangled from the pathological ones, which might reduce the specificity of HFOs to epileptic areas ( 26 , 27 ) or even result in conflicting findings ( 28 , 29 ). Recent studies have shown significant spatiotemporal overlap between HFOs and interictal epileptiform spikes ( 20 ), with a higher association to the epileptogenic regions compared to spikes or HFOs alone, promising an improved biomarker to epileptogenicity ( 12 , 30 , 31 ).…”
mentioning
confidence: 99%
“…First of all, there are physiological HFOs ( 21 ) and spurious artifacts ( 13 , 22 ) that could mimic the presence of pathological HFOs and share the same frequency range ( 23 , 24 ), which complicates the distinction of clinically relevant HFOs from artifactual or normal ones ( 25 ). When defined only by the occurrence rate, physiological HFOs cannot be disentangled from the pathological ones, which might reduce the specificity of HFOs to epileptic areas ( 26 , 27 ) or even result in conflicting findings ( 28 , 29 ). Recent studies have shown significant spatiotemporal overlap between HFOs and interictal epileptiform spikes ( 20 ), with a higher association to the epileptogenic regions compared to spikes or HFOs alone, promising an improved biomarker to epileptogenicity ( 12 , 30 , 31 ).…”
mentioning
confidence: 99%
“…Despite all these limitations, we hope to add the numerical differentiation of EEG as another way to review EEGs that include spike-associated ripples and other types of high frequencies. Because there are pitfalls of bias in the detection of scalp HFOs ( Gerner et al, 2020 ), we would like to refine the EEG differentiation method to develop a methodology to avoid such pitfalls and to make scalp HFOs a truly useful biomarker in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Each of the trials lasted for 30 seconds and was separated by a short intertrial break of equal duration. The task used was the same as described by Gerner et al (29). Participants were instructed to repeatedly type a five-digit sequence presented on the screen as fast and accurate as possible with their non-dominant hand.…”
Section: Methodsmentioning
confidence: 99%
“…It would be advantageous to be able to examine HFOs in scalp EEG, in order to make this biomarker available also to patient populations without the necessity for an invasive recording. Because of the small amplitude and local propagation characteristics of HFOs it was highly debated whether HFOs can be detected in scalp EEG (16,29). Scalp-EEG measures the summated activity of large populations of neocortical neurons and is much more prone to exogenous artifacts and noise.…”
Section: Introductionmentioning
confidence: 99%